Force Myography Sensors for Gait Phase Detection - Latsch, Bastian; Schäfer, Niklas; Schaumann, Stephan; Graffe, Steffen; Mahmoudi, Asghar; Grimmer, Martin; Altmann, Alexander A.; Dali, Omar Ben; Seiler, Julian; Rinderknecht, Stephan; Beckerle, Philipp; Kupnik, Mario (2024 IEEE SENSORS, 2024)
In human-machine interaction, muscle activity serves as an indicator of the human motion intent and is mostly assessed using electromyography (EMG). EMG requires special skin preparation, accurate electrode placement, and is affected by sweating. In contrast, force myography (FMG) measures the mechanical muscle contraction, thereby promising reliable long-term acquisition for gait phase detection. With one individual piezoelectric sensor patch per muscle, reduced cross-talk around the limb circumference is expected compared to state-of-the-art elastic straps comprising several sensors linked together. In this work, seven physically unimpaired participants wore four 3D-printed, highly sensitive ferroelectret sensors along with four EMG electrodes on the lower limbs while walking on an instrumented treadmill at normal walking speed. Tibialis anterior (TA) and vastus medialis (VM) are best suited for heel strike and toe-off detection with the FMG sensors to discriminate between swing and stance phases. The signal variability across all strides is exceptionally low. The characteristic FMG peaks differ from the ground reaction force reference by 3.6% ± 2.0% of the stride time for TA and 1.2% ± 1.2% for VM. Using the customizable ferroelectret sensors, this FMG system provides a substitute or supplement in sensor fusion for conventional EMG.
CRIS-Team Scopus Importer:2025-02-04
Keywords: ferroelectret; force myography; gait event detection; muscle activity; piezoelectric sensor; smart wearable